Risk factors for HIV virological non‐suppression among adolescents with common mental disorder symptoms in Zimbabwe: a cross‐sectional study. Issue 8 (16th August 2021) - Simms, Victoria; Bernays, Sarah; Chibanda, Dixon; Chinoda, Silindweyinkosi; Mutsinze, Abigail; Beji‐Chauke, Rhulani; Mugurungi, Owen; Apollo, Tsitsi; Sithole, Dorcas; Verhey, Ruth; Weiss, Helen A; Willis, Nicola
Abstract: Introduction: Adolescents are at increased risk of HIV virological non‐suppression compared to adults and younger children. Common mental disorders such as anxiety and depression are a barrier to adherence and virological suppression. The aim of this study was to identify factors associated with virological non‐suppression among adolescents living with HIV (ALWH) in Zimbabwe who had symptoms of common mental disorders. Methods: We utilized baseline data from a cluster‐randomized controlled trial of a problem‐solving therapy intervention to improve mental health and HIV viral suppression of ALWH. Sixty clinics within 10 districts were randomized 1:1 to either the intervention or control arm, with the aim to recruit 14 adolescents aged 10 to 19 per clinic. Adolescents were eligible if they scored ≥7 on the Shona Symptom Questionnaire measuring symptoms of common mental disorders. Multivariable mixed‐effects logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (95% CI) for factors associated with non‐suppression, defined as viral load ≥1000 copies/mL. Results: Between 2 January and 21 March 2019 the trial enrolled 842 participants aged 10 to 19 years (55.5% female, 58.8% aged <16). Most participants (N = 613) were taking an NNRTI‐based ART regimen (13 PI‐based, 216 unknown) and median duration on ART was six years (IQR three to nine years, 240 unknown). Of the 833 with viral load data 292 (35.1%) were non‐suppressed. Virological non‐suppression was independently associated with male sex (adjusted OR (aOR) = 1.43, 95% CI 1.04 to 1.97), and with not knowing one's own HIV status (aOR = 1.77, 95% CI 1.08 to 2.88), or knowing one's status but not disclosing it to anyone (aOR = 1.99, 95% CI 1.36 to 2.93), compared to adolescents who knew their status and had disclosed it to someone. Conclusions: ALWH with symptoms of common mental disorders have high prevalence of virological non‐suppression in Zimbabwe, especially if they do not know their status or have not disclosed it. In general adolescents should be informed of their HIV status, with encouragement on the beneficial health and social effects of viral suppression, to incentivise adherence. Efforts to strengthen the operationalization of disclosure guidelines for adolescents should now be prioritized.